Comparison of different doses of antigen for intradermal administration in pigs: the Actinobacillus pleuropneumoniae model - Bernardy, J; Nechvatalova, K; Krejci, J; Kudlacková, H; Brazdova, I; Kucerova, Z; Faldyna, M (Vaccine, 2008)
The intensity of antibody responses and level of protection against challenge infection induced by Actinobacillus pleuropneumoniae (APP) were compared in piglets vaccinated intramuscularly with different vaccination doses of a subunit vaccine. Secondary antibody responses to APP exotoxins induced by the intradermally administered diluted vaccines did not differ from those induced by undiluted vaccines administered either intradermally or intramuscularly. The level of protection measured by the clinical course of challenge infection to the extent of lung lesions was significantly higher in animals vaccinated with a three-time diluted vaccine in comparison with animals that were administered intramuscularly or intradermally with the most concentrated or the most diluted vaccines.
Keywords: Actinobacillus Infections; Antibodies, Bacterial; injekce intradermální; Bacterial Vaccines; Treatment Outcome; Injections, Intradermal; imunologická odpověď na dávku; antigeny bakteriální; protilátky bakteriální; prasata; plíce; Animals; Swine Diseases; Actinobacillus pleuropneumoniae; bakteriální vakcíny; Antigens, Bacterial; Dose-Response Relationship, Immunologic; Lung; nemoci prasat; zvířata; výsledek terapie; infekce bakteriemi rodu Actinobacillus; Swine